Teachers’ perceptions related to structural influences in physical education: a comparative study of Finland and the Kurdistan Region of Iraq - Mohammed, Warhel Asim; Kalari, Joonas; Makrooni, Golaleh; Lagestad, Pål (Frontiers in Education, 2025)
IntroductionPhysical education (PE) is essential for the holistic development of students due to its positive effects on their cognitive, societal, and emotional aspects. By considering the complexities of PE, teachers can assist students to achieve academic success, community well-being, and personal development, thus establishing the foundation for long-term success and sustainability.MethodsThematic analysis of PE teachers’ reflections on open-ended questions about their PE teaching revealed structural factors as a major theme. However, a lack of knowledge remains regarding how structural influences affect PE teachers’ perspectives in various socio-cultural, historical, and geographical contexts. Therefore, the purpose of this research is to provide a comparison of the different perspectives gained from PE teachers in Finland and the Kurdistan Region of Iraq (KRI). Data were gathered from 14 PE teachers: six from KRI (three men and three women) and eight Finnish (four men and four women). The average age of the Finnish group was 39 (SD: 8), with a range of 28–49 years. Teachers from KRI ranged in age from 24 to 59, with an average age of 38 (SD: 13).ResultsThe thematic analyses of the PE teachers from the two regions identified both commonalities and differences in relation to crucial structural components, such as policy frameworks, curricula requirements, resource allocations, and institutional support. Our results showed that PE teachers in Finland benefit from a nurturing atmosphere that promotes a favorable opinion of their profession. In the KRI, however, teachers encounter significant obstacles that affect their viewpoints and the quality of PE instruction.DiscussionThese findings can significantly impact the development of educational policies and strategies. The Finnish results demonstrate the effectiveness of current strategies, suggesting that further advancements in PE could improve students’ overall well-being and engagement. Conversely, the study highlighted the need for adjustments to KRI’s curriculum, teaching methodology, and policies to elevate PE’s standing and address the resource gaps that currently hinder its optimal implementation. This study also aims to identify prospective PE development sites within each of these regions.